Rachel Carson : pioneer of ecology - Kudlinski, Kathleen V.; Lewin, Ted (New York : Puffin Books, 1989)
A biography of the ecologist and writer most noted for her book "Silent Spring" concerning the dangers of pesticides and their uses.
Book Links (A.L.A.)
Publisher's Weekly
Wilson's Children
5.3
5-8
5-8
Keywords: Carson, Rachel, -- 1907-1964 -- Juvenile literature; Carson, Rachel, -- 1907-1964.; Carson, Rachel, -- 1907-1964.; Ecologists -- United States -- Biography -- Juvenile literature; Ecologists; Women -- Biography; Ecologists -- Biography; Women -- Biography